2022
DOI: 10.3390/joitmc8040200
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Technology-Organization-Environment (TOE) Framework for Online Retailing Utilization in Digital Transformation: Empirical Evidence from Vietnam

Abstract: Digital transformation has profoundly influenced various socio-economic fields and induced retailing firms to utilize digital innovations to maximize business effectiveness in the digital era. The study aims to pinpoint the motivations for online retailing (ORE) adoption and business performance among Vietnamese businesses in the formative digital transformation stage within an extended technology-organization-environment (TOE) framework. The questionnaire-based data are accumulated for this study. Firm respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 73 publications
3
52
0
2
Order By: Relevance
“…Firstly, relative advantage refers to the direct and indirect benefits that a business may derive from e-commerce. Some researchers (Gangwar et al, 2015;Mahakittikun et al, 2021;Nguyen et al, 2022) found that entrepreneurs will be more likely to adopt e-commerce if they feel they perceive a greater relative advantage. This indicates that anticipated e-commerce benefits boost e-commerce adoption.…”
Section: Technological Contextmentioning
confidence: 99%
See 4 more Smart Citations
“…Firstly, relative advantage refers to the direct and indirect benefits that a business may derive from e-commerce. Some researchers (Gangwar et al, 2015;Mahakittikun et al, 2021;Nguyen et al, 2022) found that entrepreneurs will be more likely to adopt e-commerce if they feel they perceive a greater relative advantage. This indicates that anticipated e-commerce benefits boost e-commerce adoption.…”
Section: Technological Contextmentioning
confidence: 99%
“…Therefore, compatibility for this study can be referred to as the degree to which e-commerce interacts with current firms' operations, as well as suppliers, customers, and competitors. Many studies (Eze et al, 2021;Gangwar et al, 2015;Nguyen et al, 2022;Rahman et al, 2022;Saffu et al, 2008) found that compatibility has a significant relationship with e-commerce adoption. Some other studies (Mahakittikun et al, 2021;Rahayu & Day, 2015), however, found that compatibility has a positive correlation with e-commerce adoption, but the correlation is not statistically significant.…”
Section: Technological Contextmentioning
confidence: 99%
See 3 more Smart Citations